2020
DOI: 10.1108/jhti-10-2019-0113
|View full text |Cite
|
Sign up to set email alerts
|

Connecting supplier–supplier relationships to achieve supply chain performance of restaurant companies

Abstract: PurposeThe goal of this study is to investigate how the development efficiency of restaurant companies' products of their suppliers, supplier–supplier connection, design quality and adaptation affect the supply chain performance (SCP) of restaurant companies.Design/methodology/approachWe use the stratified random-sampling method for this study. We mailed the research questionnaire to the managers in the cases where they could be identified; a total of 1,063 questionnaires were sent by mail and a useable respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 40 publications
0
23
0
2
Order By: Relevance
“…Companies in hospitality must cooperate to enhance their performance. Previous research found that improved productivity and cost reduction can be helped by better aid (Ku et al, 2020). The relationship between buyer and supplier should strengthen halal food production (Azmi et al, 2021).…”
Section: Transparencymentioning
confidence: 99%
“…Companies in hospitality must cooperate to enhance their performance. Previous research found that improved productivity and cost reduction can be helped by better aid (Ku et al, 2020). The relationship between buyer and supplier should strengthen halal food production (Azmi et al, 2021).…”
Section: Transparencymentioning
confidence: 99%
“…The SCP perspective states that enterprises develop competitive advantages according to the features of the industry in their competitive environment (Ku et al , 2020; Mackelprang et al , 2018; Morgan et al , 2018). Previous research indicated that a firm's resources for a sustainable and stable supply of products among coordinated partners, improving supply chain efficiency and coordinated operational performance are important factors to consider (McLeod, 2020; Morgan et al , 2018).…”
Section: Theoretical Background and Literature Reviewsmentioning
confidence: 99%
“…Partnership management is defined as a unique, imperfect resource where the partners are regarded as essential and continuous partnership management as the partnership develops (Khalid and Bhatti, 2015; Ku et al , 2020; Zach and Racherla, 2011). The previous study argued that the fundamental way for travel agencies to expand in Muslim geographic areas is to establish long-term partnerships with local tourism service providers (Lee and Yan, 2020; Woyo and Slabbert, 2019).…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations